Species differences in methotrexate-induced hepatotoxicity and nephrotoxicity: Rabbits resist methotrexate nephrotoxicity - Jawad H. Ahmed (The Medical Journal of Basrah University, 2016)
Background: Animal models are important tools for studying drug-induced toxicity. Species differences in drug-induced nephrotoxicity or hepatotoxicity was frequently reported, however, clear evidence of species differences in nephrotoxicity or hepatotoxicity induced by methotrexate (MTX) is not available. Aim: The present study was designed to investigate nephrotoxicity or hepatotoxicity of MTX in mice and rabbits. Methodology: twelve rabbits and 16 mice were used for the study. Each species of animals was divided into 2 groups; control and MTX treatedgroups. The control groups were treated with normal saline intra-peritoneum (IP), MTX was given IP in a dose of 20 mg/kg/weekly for 38 days for the rabbits and at a dose of 10mg/kg/ weekly for 23 days for mice. Serum levels of liver enzymes, urea, creatinine, Malondialdehyde (MDA) and MDA in liver homogenate were estimated for the rabbits. In mice, glutathione (GSH) and MDA were estimated in liver and kidney homogenates. Histopathological examination of the kidney and liver was done for the 2 species. Results: In the rabbits, MTX resulted in a significant increase in liver enzymes, and in MDA levels of serum, liver and kidney homogenates, while the levels of urea and creatinine were not affected. Histopathological changes suggestive of liver damage were seen, while the kidneys appeared normal on histopathological examination. In the mice, MTX resulted in a significant increase in MDA in the liver homogenates with a small and insignificant reduction in GSH. In mice kidney homogenates, MTX had not affected MDA, while GSH was significantly reduced. Histopathological examination in mice showed significant damage in both liver and kidney. Conclusion: MTX produced hepatotoxicity in rabbits and mice but nephrotoxicity occurred in mice only. This suggests that rabbits might be resistant to MTX induced nephrotoxicity